2022
DOI: 10.1002/efd2.5
|View full text |Cite
|
Sign up to set email alerts
|

Pectin with various degrees of esterification differentially alters gut microbiota and metabolome of healthy adults

Abstract: Pectin with various degrees of esterification (DE) leads to different food processing directions and has the distinct potential for modulating human health. Investigations of pectin-gut microbiota interactions may contribute towards better understanding of the structure-function mechanism. In this study, in vitro batch fermentation (artificial colon model) was used to illustrate the differential impacts of pectin with different DE on the gut microbiota and metabolome of healthy adults. The results indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Microbial fermentation can be affected by dietary fibers’ chemical composition and physicochemical properties [ 42 ]. All types of pectins could increase the level of acetic acid, but butyric acid was only enriched by pectin L13 [ 43 ]. Hence, the dietary fiber in tomato juice modified by HHP treatment was another possible reason for increased SCFA production.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial fermentation can be affected by dietary fibers’ chemical composition and physicochemical properties [ 42 ]. All types of pectins could increase the level of acetic acid, but butyric acid was only enriched by pectin L13 [ 43 ]. Hence, the dietary fiber in tomato juice modified by HHP treatment was another possible reason for increased SCFA production.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that low-esterified pectin could increase the biological diversity of the fecal microbiota under in vitro fermentation. 8,38…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that low-esterified pectin could increase the biological diversity of the fecal microbiota under in vitro fermentation. 8,38 Specifically, the relative abundance of Lactobacillus was significantly reduced in the mice under antibiotic treatment, while the relative abundance of Lactobacillus was restored by the administration of L102 pectin. Lactobacillus is a wellknown probiotic and has been widely used in the food industry.…”
Section: Food and Function Papermentioning
confidence: 98%
See 1 more Smart Citation
“…TAAR9 can be activated by various amines, such as N, N-dimethylcyclohexylamine, N-methylpiperidine, and triethylamine, and polyamines, especially cadaverine, putrescine, spermidine, and spermine [ 19 , 20 , 21 ]. Dietary polyamines are absorbed in the small intestine, and the gut microbiota, primarily, Bacteroides spp., Fusobacterium spp., and Clostridia [ 66 ], is the major source of polyamines in the lower part of the intestine [ 22 , 24 , 27 , 67 , 68 ]. Polyamine synthesis pathways seem to be generated in the gut microbial community, where enzymes produced by different species of bacteria collectively enable the synthesis of polyamines from precursors [ 30 , 69 ].…”
Section: Discussionmentioning
confidence: 99%